The Effect of Education Using Leaflet Media on Maternal Attitudes Toward Family Awareness of Malnutrition in Toddlers at Posyandu Nusa 1, Banjarmasin - Khairina, Salsabila Syifa Nur; Hiryadi, Hiryadi; Lisnawati, Ica; Suwandewi, Alit (Papua Medicine and Health Science, 2025)
Malnutrition in toddlers remains a common public health issue in Indonesia, including within the working area of Sungai Bilu Public Health Center in Banjarmasin. One contributing factor is the lack of maternal knowledge and attitudes regarding the importance of balanced nutrition within the family. This study aims to examine the effect of education using leaflet media on maternal attitudes toward family awareness of malnutrition. A pre-experimental design with a one-group pretest-posttest approach was employed. The sample consisted of 40 mothers with toddlers aged 1–5 years, selected through accidental sampling. The instrument used was an attitude questionnaire, and the data were analyzed using the Paired t-Test to assess differences before and after the intervention. The results showed a significant change in maternal attitudes after the educational intervention, with a p-value of 0.000. Education through leaflets was proven effective in enhancing understanding and encouraging positive attitude changes by addressing the cognitive, affective, and conative components. It can be concluded that leaflets serve as an effective and efficient educational medium for increasing maternal awareness of malnutrition prevention in toddlers. The use of leaflet media is recommended to be optimized in ongoing health promotion efforts at integrated health posts and public health centers.